Minimalistic System of Characteristics of Non-linear Baseband Pulse Devices and Its Measurement - M. A. Nazarov; E. V. Semyonov (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. The general system of parameters, including compression points and intersection points of various harmonics, is unsuitable for devices operating under the influence of baseband pulses (for example, before the modulator in the transmitter, after the demodulator in the receiver). Previously, the authors have developed simple models in the form of nonlinear recursive filters, which give a satisfactory error in describing the response of a wide class of baseband pulse circuits. The system of nonlinear functions of such models can be considered as a new system of characteristics of nonlinear-dynamical baseband impulse circuits, for which it is necessary to develop a method that ensures their measurement with an acceptable error. In the general formulation, this problem is rather challenging; therefore, this article considers only a first-order nonlinear recursive filter. However, the obtained result gives satisfactory results for devices without flat top transient overshoot.Aim. To consider a method for measuring the characteristics of nonlinear-dynamical baseband impulse devices without overshoot on the flat top of the transient response.Materials and methods. The considered recursive filter is represented by an equivalent circuit consist of nonlinear resistive and capacitive elements. Therefore, the task is reduced to measuring their current-voltage characteristics (IV) and charge-voltage characteristics (CVC). IV characteristics are measured at the flat tops of the transient characteristics of the device. Having a certain IV, we obtain the opportunity to calculate the current (and then the charge) of the capacitive element. The experimental study was carried out on the example of a three-stage amplifier with an aperiodic transient response.Results. The transient characteristics of the filter are approximated by the model with an accuracy of no worse than 3.2 %.Conclusion. The considered system of functions can be obtained with a definable error that satisfactory for practice, which allows it to be considered as a new system of parameters for nonlinear baseband pulse devices.